2014
DOI: 10.1186/s12866-014-0294-3
|View full text |Cite
|
Sign up to set email alerts
|

An ontology for microbial phenotypes

Abstract: BackgroundPhenotypic data are routinely used to elucidate gene function in organisms amenable to genetic manipulation. However, previous to this work, there was no generalizable system in place for the structured storage and retrieval of phenotypic information for bacteria.ResultsThe Ontology of Microbial Phenotypes (OMP) has been created to standardize the capture of such phenotypic information from microbes. OMP has been built on the foundations of the Basic Formal Ontology and the Phenotype and Trait Ontolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…The EMP Ontology (EMPO) for microbial environments was devised to facilitate the present analysis while preserving interoperability. Coordinated by the ENVO team, annotations from ENVO 11,51 , UBERON (metazoan anatomy) 57 , PO (Plant Ontology) 58 , FAO (Fungal Anatomy Ontology, purl.obolibrary.org/obo/fao.owl), and OMP (Ontology of Microbial Phenotypes) 59 were mapped to our EMPO levels 2 and 3 (empo_2 and empo_3). Additionally, the free-living or host-associated lifestyles were captured in level 1 categories (empo_1).…”
Section: Methodsmentioning
confidence: 99%
“…The EMP Ontology (EMPO) for microbial environments was devised to facilitate the present analysis while preserving interoperability. Coordinated by the ENVO team, annotations from ENVO 11,51 , UBERON (metazoan anatomy) 57 , PO (Plant Ontology) 58 , FAO (Fungal Anatomy Ontology, purl.obolibrary.org/obo/fao.owl), and OMP (Ontology of Microbial Phenotypes) 59 were mapped to our EMPO levels 2 and 3 (empo_2 and empo_3). Additionally, the free-living or host-associated lifestyles were captured in level 1 categories (empo_1).…”
Section: Methodsmentioning
confidence: 99%
“…Other resources outside of GO have modeled their annotation capture systems on the GAF format. For example, the Ontology of Microbial Phenotypes [ 17 ] uses a modifi ed version of the GO GAF, but employs ECO terms instead of GO evidence codes. The full use of ECO terms by the GO would enhance the integration of data derived from such diverse sources.…”
Section: Eco Terms Versus Go Codesmentioning
confidence: 99%
“…More recently it has been shown that at least one CRISPR-associated 38 (Cas) protein can suppress non-homologous end-joining (NHEJ) DNA repair, 39 which may lead to selection against having CRISPR in some taxa [21]. In or- 40 der to determine the relative importances of these different mechanisms, we 41 must first identify the habitats and microbial lifestyles associated with CRISPR 42 immunity. 43 Here we aim to expand on previous analyses of CRISPR incidence in three 44 ways: (1) by drastically expanding the number of environmental and lifestyle 45 traits considered as predictors using the combination of a large prokaryotic trait 46 database and machine learning approaches, (2) by incorporating appropriate 47 statistical corrections for non-independence among taxa due to shared evolu- 48 tionary history, and (3) by simultaneously looking for patterns in RM systems, 49 which will help us untangle the difference between environments that specifically 50 favor CRISPR adaptive immunity versus DNA-degrading intracellular immune 51 systems in general (RM and CRISPR).…”
Section: Introductionmentioning
confidence: 99%
“…With the number of microbial genomes in public databases con-338 stantly expanding, so too should efforts to provide metadata about each of the 339 organisms represented by those genomes. At least part of the problem lies in the 340 lack of a universally accepted controlled vocabulary for microbial traits (sim-341 ilar to that provided by the Gene Ontology Consortium [39]), although some 342 admirable attempts have been made [40,41]. This would both facilitate the 343 construction of more expansive trait databases, and would help deal with the 344 issue of comparing traits that span many different scales.…”
mentioning
confidence: 99%